2021
DOI: 10.3390/vaccines9020117
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Related Errors in Reconstitution in South Korea: A National Physicians’ and Nurses’ Survey

Abstract: Vaccine-related errors (VREs) result from mistakes in vaccine preparation, handling, storage, or administration. We aimed to assess physicians’ and nurses’ experiences of VREs in South Korea, focusing on reconstitution issues, and to understand the barriers to and facilitators of preventing them. This was a cross-sectional study using an internet-based survey to examine experiences of reconstitution-related errors, and experience or preference with regard to ready-to-use vaccines (RTU) by physicians and nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
2
5
0
2
Order By: Relevance
“…In addition, due to the requirement for reconstitution and additional associated steps, additional errors such as ‘Lack of cleansing of vials rubber stopper after removing the plastic flip off’ or ‘Vial content (adjuvant or reconstituted vaccine) not fully aspired into syringe’ were observed. This is in line with other published studies [13, 16]. A survey-based evaluation of vaccine related errors by Lee et al found 76.4% of physicians and 41.5% of nurses experienced errors related to reconstitution, including ‘vial contents not aspired into syringe’ (52.0% and 14.7%, respectively), ‘inadequate shaking’ (51.6% and 19.1%, respectively), ‘spillage or leakage during reconstitution’ (42.4% and 14.7%, respectively), ‘needle twisted when inserted in vial stopper’ (29.6% and 11.8%, respectively), ‘same needle used for reconstitution and injection’ (23.2% and 10.0%, respectively), ‘forgetting to reconstitute’ (19.2% and 7.6%, respectively), ‘other’ (31.6% and 11.1%, respectively) [16].…”
Section: Methodssupporting
confidence: 94%
See 2 more Smart Citations
“…In addition, due to the requirement for reconstitution and additional associated steps, additional errors such as ‘Lack of cleansing of vials rubber stopper after removing the plastic flip off’ or ‘Vial content (adjuvant or reconstituted vaccine) not fully aspired into syringe’ were observed. This is in line with other published studies [13, 16]. A survey-based evaluation of vaccine related errors by Lee et al found 76.4% of physicians and 41.5% of nurses experienced errors related to reconstitution, including ‘vial contents not aspired into syringe’ (52.0% and 14.7%, respectively), ‘inadequate shaking’ (51.6% and 19.1%, respectively), ‘spillage or leakage during reconstitution’ (42.4% and 14.7%, respectively), ‘needle twisted when inserted in vial stopper’ (29.6% and 11.8%, respectively), ‘same needle used for reconstitution and injection’ (23.2% and 10.0%, respectively), ‘forgetting to reconstitute’ (19.2% and 7.6%, respectively), ‘other’ (31.6% and 11.1%, respectively) [16].…”
Section: Methodssupporting
confidence: 94%
“…Agreement between reviewers of ≥80% was considered acceptable, and no changes were needed based on quality control. The vaccine-specific error checklist was developed by reviewing all steps listed in the label of approved vaccines and were cross referenced with published literature [13, 16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prevalent errors were inadequate interval between vaccines, followed by vaccines administered outside the recommended age. Studies also corroborated these findings ( 9 , 11 , 18 , 23 ) . Health professionals’ lack of knowledge about the recommended intervals and minimum intervals between vaccines exposes them to immunization errors.…”
Section: Discussionsupporting
confidence: 62%
“…One of them (Hexacima/Hexaxim/Hexyon) is a ready-to-use, fully liquid product that can be rapidly and safely administered skipping the reconstitution step as required for the pentavalent vaccines that are now registered and in use in South Korea [ 12 , 13 ]. With its ready-to-use status, this hexavalent vaccine type prevents several types of immunization errors that may happen [ 14 ]. A previous study has demonstrated that medical errors may occur most frequently during the reconstitution step [ 15 ].…”
Section: Introductionmentioning
confidence: 99%